Wikipedia as one of the Tools Of Information War And Influence On The Educational System - R. Garifullin, Ramil; Kazan federal university (2017)
The article analyzes Wikipedia as one of the problem components of national information security of different countries, and as a factor of influence on the educational system. We considered all components of this problem. We proposed ways to solve this problem. Wikipedia should be politically indifferent. The true encyclopedia is an encyclopedia of timeless and eternal knowledge, and the present is not yet encyclopedic and controversial. Something that is being established should not be the basis for Wikipedia content (political topics, etc.). How can we make it so that Wikipedia is just a collection of truths, rather than a site of conflicts and disputes, particularly interethnic ones?